Chemical composition and antibacterial activity of medicinally useful essential oil from the Rhizomes of alpinia allughas rosc. - NIKHIL KUMAR; VIJAYATA (International Journal of Pharma and Bio Sciences, 2017)
To obtain much better information about the medicinally useful essential oil of the rhizome of Alpinia allughas Rosc., the oil from the rhizome collected from Guwahati, Assam, has been isolated by hydrodistillation and analysed by GC and GC/MS. Twenty-eight compounds representing 95.14% of the oil have been identified. Norisoprenoid related antioxidant β-ionol is the major component (15.53%). In a rare observation, the sesquiterpenes & derivatives (39.47%) and monoterpenes & derivatives (39.42%) are almost in equal amounts. Among the monoterpenes & derivatives, the terpinen-4-ol (11.51%), 1,8-cineole (8.91%) and fenchyl acetate (7.55%) are main. Among sesquiterpenes & derivatives, the major components are found to be β-selinene (13.77%) and γ-elemene (6.30%). The oil shows good antibacterial activity against Staphylococcus aureus.